Supply Chain Management of Zakat to Reduce Poverty and Improve Community Welfare (Case Study Baznas in Serang District) - Faridatul Fauziah (International Journal of Supply Chain Management, 2020)
Abstract- Within the increasingly competitive markets and the rapid changes in business all over the world today, it has become imperative for organizations to reconsider supply chain management (SCM) strategies due to the fact that the same SCM strategy may not appropriate for all organizations. This research conducted on the existence of alms, infaq, and charity institutions in Serang district and poverty of the people whose existence must be considered in the aspect of life, the potential for improving education for the poor. The research method is carried out with a qualitative approach. The technique of collecting data uses observation, interviews and documentation. The results of the study show that one effort through empowering the collection of zakat funds from the community through Zakat al-Fitr, professional zakat and zakat mall is very potential if it can be used to provide capital and distribute zakat in a professional, systematic and transparent manner by prioritizing honesty and removing personal interests and group so that zakat can be distributed according to the program that has been implemented at BAZNAS institution in Serang regency base on the arrangement stated in Law No. 23 year 2011. Whether in implementing the zakat law it is in accordance with its purpose for the welfare of the people's economy and alleviating poverty.